The Impact of the COVID-19 Pandemic on Forensic Mental Health Services and Clinical Outcomes: A Longitudinal Study - Puzzo, Ignazio; Aldridge-Waddon, Luke; Stokes, Nicholas; Rainbird, Jordan; Kumari, Veena (Frontiers in Psychiatry, 2022)
Abstract Background The COVID-19 pandemic has had a substantial impact on forensic mental health services provision and implementation. This study aimed to provide an analysis of the impact of COVID-19 related restrictions on routine outcomes within a large forensic mental service in London, UK. Method We conducted a longitudinal cohort study using routinely collected data-sets pre (April 2018 - March 2020) and during the pandemic (March 2020 – March 2021; lockdown periods, January-March 2021, 8th March-May 2020; January-March 2021). We used causal impact models (Bayesian structural time-series) to examine the effect of the COVID-19 related changes in service provision and implementation routine outcomes. Results There was an overall increase in long-term segregation (LTS) hours during the pandemic; 130%, (95% Cl 87%, 171%) during Lockdown 1; 113%, (95% Cl 74%, 151%) during post-Lockdown 1; 157% (95% Cl 116%, 197%) during Lockdown 2 and, finally, 69% (95% Cl 49%, 92%) during Lockdown 3. Non-physical assaults to staff decreased, (-41%, 95% Cl -83%, 0.97%) during Lockdown 1. Physical assaults to staff decreased (-48%, 95% CI -92%, 6.1%) but physical and non-physical assaults to service users (199%, 95% CI 57%, 355%), (199%, 95% CI 59%, 345%), self-harm (325%, 95% Cl 137%, 487%) and enforced medication (140%, 95% Cl 48%, 224%) all increased during Lockdown 3. Overall, the most negative outcome was evident during Lockdown 3. Conclusion The pandemic and its related restrictions have negatively affected some service outcomes resulting in increased incidents of violence and increase in some restrictive interventions beyond what would have been expected had the pandemic not happened.